FOOD CULTURE ACCULTURATION OF MARTABAK CUISINE ORIGINALLY FROM INDIA TO INDONESIA - Angelina Rianti (Studi Budaya Nusantara, 2018)
AbstractMartabak is a popular street food snack that is easy and widely found in the countries of India, Indonesia, Saudi Arabia, and Malaysia. Martabak was first introduced in India, precisely in the region of Kerala. Martabak is an appetizer, side dish or some kind of snack. Indian traders and people who migrate to other countries bring and introduce martabak and become as a process of acculturation of food culture. Martabak itself introduced from India as a dish of stuffed fried bread with topping like meat and vegetables with main ingredient of eggs. In Indonesia, the culture of martabak food is adjusted and modified to form a new sweet martabak textured like pancake that has a thicker texture than savoury martabak. In Saudi Arabia, martabak is also known as two types which are sweet and savoury and often referred as "mutabbaq", while in Malaysia, sweet type of martabak known as "apam balik". AbstractMartabak adalah jajanan popular yang mudah dan banyak ditemukan di negara India, Indonesia, Arab Saudi, dan Malaysia. Awal mulanya martabak diperkenalkan di negara India, tepatnya di wilayah Kerala. Makanan ini diperkenalkan sebagai hidangan pembuka, hidangan sampingan, atau sejenis kudapan. Para pedagang dan warga India yang bermigrasi ke negara lain membawa dan memperkenalkan hidangan ini dan menjadi sebuah proses akulturasi budaya pangan. Martabak sendiri diperkenalkan dari India sebagai sajian roti goreng yang diberi isian seperti daging dan sayur dan bahan utama telur. Di Indonesia, budaya pangan martabak disesuaikan dan dimodifikasi hingga terbentuknya martabak manis seperti panekuk yang memiliki tekstur lebih tebal dari martabak asin. Di Arab Saudi, martabak juga dikenal dua jenis, yaitu manis dan asin yang sering disebut sebagai “mutabbaq”, sedangkan di Malaysia, martabak berjenis manis dikenal dengan “apam balik”.